Equality in managing service delivery - Collier, Rohan, 1945- (Buckingham ; Philadelphia : Open University Press, 1998)
This book is divided into eight parts: Why equal opportunities in service delivery?; How services can discriminate; What the law requires; Identifying needs: involving the public; Developing and implementing equal opportunities policies in service delivery; Developing performance indicators and monitoring for equalities; Reviewing and chinging services; and Barriers to achieving equalities in service delivery.
Keywords: Managing; Customer services; Discrimination; Customer services -- Moral and ethical aspects -- Great Britain; Discrimination -- Great Britain